The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0035-9203(01)90164-6
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole therapy and reduced decline in haemoglobin concentration during pregnancy (Sierra Leone)

Abstract: WHO recommends that anthelmintic treatment be included in strategies to improve maternal nutrition in areas where hookworms are endemic and anaemia is prevalent. At present, few countries have adopted this recommendation, partly owing to the lack of data to support the adverse effects of hookworms on maternal health. A longitudinal study was conducted on 125 women in Sierra Leone (in 1995/96) to measure the impact of single-dose albendazole (400 mg) and daily iron-folate supplements (36 mg iron and 5 mg folate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 12 publications
6
66
0
Order By: Relevance
“…It was found that the drug minimised the decline in haemoglobin and serum ferritin concentrations during pregnancy without any extra negative effect on newborns. 43,44 It was therefore concluded that pregnant women in this part of Africa would benefit from antihelminthic treatment after the first trimester and regular iron-folate supplements during the first trimester. After a thorough review of information about antihelminthic drugs (albendazole, levamisole, mebendazole and pyrantel) and with due regard to the seriousness of hookworm infection during pregnancy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the drug minimised the decline in haemoglobin and serum ferritin concentrations during pregnancy without any extra negative effect on newborns. 43,44 It was therefore concluded that pregnant women in this part of Africa would benefit from antihelminthic treatment after the first trimester and regular iron-folate supplements during the first trimester. After a thorough review of information about antihelminthic drugs (albendazole, levamisole, mebendazole and pyrantel) and with due regard to the seriousness of hookworm infection during pregnancy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies in Nepal, among populations perhaps poorer and less well nourished than ours (as indicated by items owned, anthropometry and vitamin A status (Dreyfuss et al, 2000) and with a traditionally vegetarian diet (Bondevik et al, 2000)), anaemia showed a significant association with hookworm infection (Bondevik et al, 2000; Dreyfuss et al, 2000). The effects of hookworm infection are partially mediated by iron deficiency (Bondevik et al, 2000; Olsen et al, 1998) and in the trial conducted in Sierra Leone iron-folate supplements had a greater benefit for anaemia in pregnancy than treatment with albendazole (Torlesse and Hodges, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…11,[13][14][15] National governments, healthcare practitioners and helminth control program managers should be confident in the routine inclusion of these anthelminthics in antenatal care programs in areas where hookworm infection meets the threshold prevalence set by WHO (ie, Ͼ20 -30%).…”
Section: Discussionmentioning
confidence: 99%
“…Three were observational studies examining mebendazole 10,13,14 and one was a randomized, controlled trial of albendazole. 15 None of these studies found significantly more adverse outcomes in the benzimidazole group compared with the comparison group. However, because of limitations in study design and methodology (eg, small sample sizes, unknown or nonstandard dosages, possibility of information and selection biases) and a lack of detail in the ascertainment or reporting of the adverse outcomes, a new and rigorous evaluation was warranted.…”
mentioning
confidence: 97%